From the factory to the city: the architectonic circulation as a social agent - Sáez, Javier (Universidad Nacional de Mar del Plata. Facultad de Arquitectura, Urbanismo y Diseño, 2009)
Among the issues in which one sees the influence of the urban over the architecture it is the way to understand the movement of the people. It deals with the way that, unlike the taylorised movement which was driven by the functionalism, it takes the city and the community relations that it promotes as a model, setting up building circulation as interior streets, with cross roads and plazas: the circulation relationship strategy. This strategy pursuits to reproduce a fundamental urban attribute: its dynamic relationship, its configuration as a place of connection and exchange. It deals with the issues that on the last third part of the XX century it was blurred by the presence of other ways of vehicular relationship driven buy new supports of exchange and communication. Fact that also impacts on the shape of the movement in architecture and conducts the project of a second generation of the relationship strategy.